Editors’ Remarks - Lauter, Jenna; Ortlip-Sommers, Sarah (Columbia Journal of Gender and Law, 2021)
These remarks by our editors opened and closed the Are You There Law? It’s Me, Menstruation Symposium Conference on April 9 and 10 of this year. Amidst the global pandemic, participants gathered virtually on Zoom for two days of engaging presentations by our Symposium authors and vibrant discussions among scholars, practitioners, and students alike.